The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1051/matecconf/201815005086
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse in Academic Writing of Pre-University Arab Students at the International Islamic University Malaysia (IIUM)

Abstract: Abstract. There is lack of studies on the use of metadiscourse markers; especially amongst international students studying in Malaysia and Malaysia are receiving scores of international students particularly from the Middle East annually. This study involves a textual analysis of students' academic writing where the metadiscourse markers in 50 Arab IIUM students' academic texts were identified and analyzed. The findings of this study indicated that Arab writers had a greater inclination for the deployment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…From those findings, it is clearly seen that the total occurrence of metadiscourse markers in introduction sections of Unimus EFL learners is 637 in which the interactive metadiscourse usage is higher (524) than interactional metadiscourse one (113). This finding is an alignment with the previous findings (Anwardeen, Luyee, Gabriel & Kalajahi, 2013;Zakaria & Malik, 2017) which showed that undergraduate students tended to use interactive metadiscourse (textual metadiscourse) rather than interactional metadiscourse (interpersonal metadiscourse). It means that the learners, in this case, tend to interpret the messages explicitly through the text rather than involving the readers through the arguments given.…”
Section: Metadiscourse Markers Frequently Used By Unimus Efl Learnerssupporting
confidence: 91%
“…From those findings, it is clearly seen that the total occurrence of metadiscourse markers in introduction sections of Unimus EFL learners is 637 in which the interactive metadiscourse usage is higher (524) than interactional metadiscourse one (113). This finding is an alignment with the previous findings (Anwardeen, Luyee, Gabriel & Kalajahi, 2013;Zakaria & Malik, 2017) which showed that undergraduate students tended to use interactive metadiscourse (textual metadiscourse) rather than interactional metadiscourse (interpersonal metadiscourse). It means that the learners, in this case, tend to interpret the messages explicitly through the text rather than involving the readers through the arguments given.…”
Section: Metadiscourse Markers Frequently Used By Unimus Efl Learnerssupporting
confidence: 91%
“…Dialectical argumentation makes it possible to place arguments in favor of and against the thesis under consideration, which entails the use of argumentation methods. In this regard, as noted by Zakaria and Malik (2018), a defensible subject must know the recipient. Therefore, it is necessary to know one's own environment, to know which theses they accept or reject, as well as to be aware of their identity and values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students need to develop argumentation skills for the correct expression of their thoughts, protection of their ideas, and communication (Barrot & Gabinete, 2019). In this perspective, the theory of argumentation is a line of research that is of growing interest in the 21st century in the educational, linguistic and cognitive sciences, as well as among teachers of foreign languages and researchers in the field of bi-multi-literacy (Zakaria & Malik, 2018). Thus, the purpose of this study is to analyze the implementation of a metadiscursive didactic consistency when writing an argumentative essay in English as a second language.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, Lenk (1998) argued that writers, unlike speakers, have a space to plan their text propositions showing ''appropriate indexing of what comes next and how it is related to the overall scheme of writing'' (p. 18), producing a relatively smooth and clear topic development. For Zakaria and Abdul Malik (2018) and Silva (1990), a written text can be examined from three perspectives. The first perspective is cognitivepsychological which figures out a written text as a recorder of the writer's psychological status forming a general attitude.…”
Section: Written Textmentioning
confidence: 99%
“…2022; Carrio-Pastor, 2022;Liao, 2020;Bal-Gezegin & Bas, 2020;Takač & Ivezić, 2019;Duruk, 2017;Hyland, 2002Hyland, , 2005Jones, 2011;Hyland & Tse, 2004;Swales, 1990) touched upon errors of language learner from an explicit discourse standpoint, showing, for example, sources of problems of cohesion, coherence, use of discourse markers, etc., and ignoring implicit sources of language learner problems. Even those studies that examined the errors of language learner (e.g., Zakaria & Abdul Malik, 2018;Zali et al, 2020;Mina & Biria, 2017) from an interpersonal perspective, they are still in the stream of explicitness of dealing with sources of errors. In other words, all these studies examined the language learner from a microlevel metadiscourse standpoint.…”
mentioning
confidence: 99%